The effect of a proposed training curriculum in developing the skill competence of young boxers - Jaffer, Ammar Mosa; Ahmed, Saif Saad; Bakee, Muna Zaidan; Ahmed, Omar Saad (International Journal of Psychosocial Rehabilitation, 2020)
Boxing is a sports game that depends, like other sports, on the scientific fields as a basis for developing and reaching it to high levels, as it is distinguished from other sports by the various technical movements of the arms, torso, and legs in which the reaction plays a large role of accuracy and speed, as well as focus for an elaborate response. Boxing is one of the individual games where winning requires obtaining the largest number of points by paying the most possible amount of punches and the permissible areas that are (face, chest and abdomen) and this requires skill and physical efficiency and the application of high plans that contribute to increasing the capabilities of the boxer to obtain the largest A possible number of points and more punches is the focus of the research problem addressed by the researcher in his training method. The problem of research, which is represented by the method of arbitration and the calculation of points, and through the researcher’s follow-up of local championships and the Iraqi boxers’ struggles in external meetings, as the researcher noted that there are deficiencies in some boxers in investing all permitted punching areas, as the boxers rely very heavily in paying their punches to the facial areas, which is an area Small, leaving the chest. In the last ten years, the boxing game witnessed a great development after the adjustments that took place on the abdomen, which is a larger area as a target or is paid to it more punches compared to the head and face and assumptions that the opposite is true. This performance negatively and very significantly affects the outcome of the fight, hence the researcher’s vision to develop a proposed training curriculum through which the competence of boxers is developed to reach and invest all areas permitted in punching to obtain the largest possible number of points, which in turn is reflected in the outcome of the fight and in a positive way. Research Objectives: Establish a training curriculum to develop all boxers in punching the legally permitted areas. Knowing the effect of the training curriculum on the development of all boxers in punching the legally permitted areas. Research hypotheses: There is a positive effect of the proposed training approach on the competence of skilled boxers in punching all areas of the body permitted by law. There is a positive impact of the proposed training approach on the results of the skillful boxers. Chapter Three: Research Methodology and Field Procedures: The researcher used the experimental approach in the manner of equal groups, as the sample members were (24) boxers. After conducting the pre-test tests, for both groups, the vocabulary of the training curriculum was applied to the experimental group. It took (8) weeks at an average of (8) units per week. After the end of the training curriculum, skill tests were conducted. The researcher used the statistical bag (SPSS) for the purpose of statistical data processing. Chapter Four: Presenting, analyzing and discussing the results: This section contained the presentation of the results in graphical forms and then their analysis, where the results were extracted through the use of appropriate statistical treatments from an arithmetic medium and for a standard deviation and test (T) for analogous and asymmetric samples. They were discussed in a scientific manner supported by scientific sources and the researcher reached through his discussion to Achieve two research goals and hypothesis. Chapter Five: Conclusions and Recommendations: Through discussion of the results presented, the researcher reached many conclusions and recommendations